385 USE OF LIPID LOWERING THERAPY IS ASSOCIATED WITH IMPROVED HDL FUNCTION IN METABOLIC SYNDROME AND CORONARY HEART DISEASE PATIENTS, EVEN WITH COMPARABLE LDL, HDL, AND TRIGLYCERIDE LEVELS. (1st January 2005) - Watson, K. E.; Hama, S.; Harris, J.; Ansell, B. J.; Fonarow, G. C.; Navab, M.; Fogelman, A. M.
Abstract : Background: Patients with the metabolic syndrome (Met Syn) and with coronary heart disease (CHD) are at high-risk for future cardiac events and we have shown that these populations have pro-inflammatory HDL. Because lipid lowering decreases cardiac events, we hypothesized that use of lipid lowering medications in these populations would be associated with decreased pro-inflammatory HDL. Methods and Results: We studied 17 adults presenting to a lipid disorders clinic with either Met Syn or CHD, who were matched for LDL, HDL and triglyceride levels. Patients were classified into 3 groups based on lipid lowering therapy used continuously for the prior 6 weeks: no lipid lowering therapy (no Tx; n=7), statin only (S; n=5), or statin + niacin (S+N; n=5). We measured plasma lipoproteins, and also determined the inflammatory/anti-inflammatory properties of HDL by the ability of subjects' HDL to alter LDL-induced monocyte chemotactic activity (MCA) in an artery model. MCA induced by a standard LDL sample was normalized to 1.0 and MCA values ≥1 after the addition of subjects' HDL indicated pro-inflammatory HDL; values ≤1 were anti-inflammatory. Patients on no treatment tended to be younger than S or S+N groups (mean age 42, 51, 52 yrs., respectively). LDL was comparable in all groups (no Tx = 126 mg/dL ± 42; S = 117 ± 56; S+N = 110 ± 31; p = NS for all). HDL levels were also comparable in all groups (no Tx = 37 mg/dL ± 13; S = 37 ± 9; S+N = 38 ± 6; p = NS for all). Triglycerides were not different between the groups. Patients on no therapy had significantly more pro-inflammatory HDL (MCA = 2.30±0.97) than those on statin alone (MCA = 1.23±0.10, p=0.027); or those on statin +niacin (MCA = 1.19±0.31, p=0.022). MCA was not different between the S and S+N groups. Conclusion: Patients with either Met Syn or CHD on lipid lowering therapy had significantly less pro-inflammatory HDL as compared to LDL, HDL and triglyceride level matched patients not on lipid lowering therapy. These results suggest that the decreased coronary risk seen in patients on lipid lowering therapy may, at least in part, be related to a reduction in pro-inflammatory HDL.